2022
DOI: 10.18502/ijph.v51i2.8689
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Carcinogenic Genes in Colon Adenocarcinoma

Abstract: Background: We aimed to probe carcinogenic genes associated with colon adenocarcinoma (COAD) development. Methods: The gene expression profile of COAD were downloaded from TCGA. Differentially expressed genes (DEGs) were identified; GO and KEGG pathway enrichment were analyzed. Applying the up-mRNA-and-down-miRNA pairs and the down-mRNA-and-up-miRNA pairs, the miRNA target network was generated. The important genes were further analyzed towards the influence on overall survival and immune infiltration. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Furthermore, we found that tea consumption interacted with gene sets overrepresented in keratinization, keratin filament, and intermediate filament pathways. These pathways are involved in the antiacne activity of epigallocatechin-3-gallate, which is a major polyphenol in green tea and observed to be enriched in onset of colon cancer . Previous studies suggested the association of long-term alcohol consumption with poor semen quality due to oxidative stress and genotoxicity on hormonal regulation and DNA integrity .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, we found that tea consumption interacted with gene sets overrepresented in keratinization, keratin filament, and intermediate filament pathways. These pathways are involved in the antiacne activity of epigallocatechin-3-gallate, which is a major polyphenol in green tea and observed to be enriched in onset of colon cancer . Previous studies suggested the association of long-term alcohol consumption with poor semen quality due to oxidative stress and genotoxicity on hormonal regulation and DNA integrity .…”
Section: Discussionsupporting
confidence: 89%
“…These pathways are involved in the antiacne activity of epigallocatechin-3-gallate, which is a major polyphenol in green tea 52 and observed to be enriched in onset of colon cancer. 53 Previous studies suggested the association of long-term alcohol consumption with poor semen quality due to oxidative stress and genotoxicity on hormonal regulation and DNA integrity. 54 In addition, PRM1 is associated with proliferation, invasion, and migration of colon cancer cells, 55 and male infertility also shares its genetic cause with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of COAD is related to a variety of factors, including disease stage, age, gender, and so on. With the development of sequencing technology, studies have proved that gene expression patterns are also related to disease prognosis [4]. N6-methyladenosine (m6A) is a common and conserved transcriptome modi cation in higher eukaryotic cells [5].…”
mentioning
confidence: 99%